Pengaruh Pendekatan Permainan untuk Pemanasan terhadap Minat Siswa dalam Mata Pelajaran PJOK - Hendrawan, Kahan Tony; Sulistyo, Yully Wahyu (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to see the effect of games to warm up on students' interest in learning in PJOK, the method with type of experimental research with descriptive quantitative (One Group Pretest Posttest Design). Class IV as a population and sample determination with purposive sampling based on the main criteria in the category class IV and including MI Al Hikmah students, instruments with a questionnaire learning interest with 35 questions, Data analysis using descriptive statistics and t-test (different test). The initial data results see the results of the pre test and post test in the medium category then see the difference test get the results significance with the Paired Samples Test sig value 0.00 <0.05, so it can be concluded that there is an effect of the game approach to warm up on interest in learning PJOK.